1999
DOI: 10.1046/j.1464-5491.1999.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of hepatitis C virus infection in Greek diabetic patients

Abstract: It remains a strong hypothesis that diabetic patients are at increased HCV infection risk, yet our findings in Greek diabetic patients were rather low. Further studies, possibly multicentre, are needed to estimate prevalence and address the question of whether a direct effect of HCV in diabetes development does actually exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
3
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 9 publications
6
41
3
4
Order By: Relevance
“…The present study was not able to reveal a difference in the frequency of infection by HCV between diabetics and non-diabetics, which is in agreement with the studies by Mangia et al [7], Sotiropoulos et al [8], Virseda et al [9] and Wolff et al [10]. On the other hand, this feature is in disagreement with the studies that found a higher prevalence of HCV infection in type 2 diabetic patients [2,[4][5][6].…”
Section: Hepatitis C Infection In Diabetic Patientscontrasting
confidence: 56%
See 2 more Smart Citations
“…The present study was not able to reveal a difference in the frequency of infection by HCV between diabetics and non-diabetics, which is in agreement with the studies by Mangia et al [7], Sotiropoulos et al [8], Virseda et al [9] and Wolff et al [10]. On the other hand, this feature is in disagreement with the studies that found a higher prevalence of HCV infection in type 2 diabetic patients [2,[4][5][6].…”
Section: Hepatitis C Infection In Diabetic Patientscontrasting
confidence: 56%
“…In order to justify screening for HCV in diabetics patients other indicative features for this infection should be considered, such as altered levels of aminotransferases or other signs of liver disease [8,15].…”
Section: Hepatitis C Infection In Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain negative data that are not in agreement with an association between HCV infection and T2DM have also been reported [97][98][99][100][101][102][103][104] . However, the number of published epidemiological studies that are in agreement with the association between HCV infection and T2DM is higher than the number of studies in disagreement with this hypothesis.…”
Section: Development Of T2dmmentioning
confidence: 99%
“…It is now clear that hepatitis C conveys a risk for developing DM, in particular type 2 [5][6][7] . Moreover, several studies have found a high prevalence of anti-HCV antibodies among patients with diabetes, especially those with type 2 DM [8][9][10][11][12][13] ; however, some authors have not observed an association between HCV infection and diabetes [14][15][16] . Since effective therapy has become available for HCV, it may be worthwhile to determine virus prevalence in patients with and without diabetes, in order to decide whether a programme for screening should also focus on type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%